2016
DOI: 10.1007/s11356-016-6946-0
|View full text |Cite
|
Sign up to set email alerts
|

Distribution, fate, and risk assessment of antibiotics in five wastewater treatment plants in Shanghai, China

Abstract: The project studied the occurrence, fate, and seasonal variation of 14 antibiotics, from five wastewater treatment plants (WWTPs) in Shanghai. The results indicated that ofloxacin, sulfamethoxazole, and oxytetracycline were the predominant antibiotics, with maximum concentrations of 1208.20, 959.13, and 564.30 ng/L in influents, while 916.88, 106.60, and 337.81 ng/L in effluents, respectively. The level of antibiotics in WWTPs obviously varied with seasonal changes, and higher detectable frequencies and concen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(12 citation statements)
references
References 46 publications
1
10
1
Order By: Relevance
“…for most wastewater in Spain and other parts of the world (Martín et al, 2011;Wu et al, 2016). In fact, the occurrence of these compounds in influent water in Europe, America and Asia has been reported rarely and always at low concentrations (< 107 ngL -1 ) (Kuster et al, 2008;Tran et al, 2018;Zhang et al, 2017).…”
Section: Wastewatermentioning
confidence: 99%
“…for most wastewater in Spain and other parts of the world (Martín et al, 2011;Wu et al, 2016). In fact, the occurrence of these compounds in influent water in Europe, America and Asia has been reported rarely and always at low concentrations (< 107 ngL -1 ) (Kuster et al, 2008;Tran et al, 2018;Zhang et al, 2017).…”
Section: Wastewatermentioning
confidence: 99%
“…Research has shown that the spread of multidrug resistant bacterial strains and their potential adverse effects on animals and environment are closely associated with the abuse of antibiotics [6,7]. Numerous studies have reported the detection of antibiotics in coastal water and wastewater at concentrations from μg/L to mg/L levels [8]. Furthermore, antibiotic resistant genes harbored by mobile genetic elements have proven to be transferred between bacteria and the environment [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…Levofloxacin, SMZ, and 17α‐E2 were the predominant components in the treated sewage, with average concentrations of 15.2 ± 11.2, 3.60 ± 4.29, and 3.52 ± 0.94 ng L −1 , respectively. High LVX and SMZ concentrations were also detected in the effluent of STPs in Japan, Beijing, Chongqing, and Shanghai (Ghosh, Okuda, Yamashita, & Tanaka, 2009; Wu et al., 2016; Yan et al., 2014). Estrogen concentrations in the effluent in this work were lower than those found in North America, Europe, and Asia (Adeel, Song, Wang, Francis, & Yang, 2017).…”
Section: Resultsmentioning
confidence: 99%